Bridging Vision and Reality:Public Policy and the Implementation Gap in India’s NEP 2020 (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The National Education Policy 2020 (NEP 2020) represents one of the most ambitious educational reform initiatives undertaken in India in the past three decades. Conceived as a transformative framework, the policy seeks to restructure the Indian education system by promoting multidisciplinary learning, flexibility in academic pathways, integration of vocational education, and the adoption of technology-driven educational practices. However, the success of any public policy is determined not only by the clarity of its vision but also by the effectiveness of its implementation at the institutional level. This study examines the implementation of NEP 2020 within undergraduate colleges affiliated with the University, focusing on the gap between policy design and institutional execution. Employing a mixed-methods research design, the study draws on quantitative survey data and qualitative insights gathered from ten affiliated colleges—two urban and eight rural institutions. The findings reveal significant structural and administrative challenges that hinder effective implementation, including inadequate infrastructure, shortages of trained faculty, limited digital readiness, and an overburdened examination system. Furthermore, the study highlights the complexities of implementing national-level reforms within a federal governance structure where educational policy is centrally formulated but largely executed by state-level institutions. The analysis suggests that while NEP 2020 provides a visionary blueprint for educational transformation, its success depends heavily on institutional preparedness, sustained financial investment, and coordinated policy execution across governance levels. Bridging the implementation gap is therefore essential to realize the transformative potential envisioned by NEP 2020.